Pengaruh Program Desa Wisata Terhadap Peningkatan Pendapatan Masyarakat (Studi Kasus Di Desa Bejiharjo, Kabupaten Gunung Kidul) - Yoga Aditya; Sri Muljaningsih (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study  aimed to:  (1) determine  the effect  of  tourist village  program toward  the enhancement people’s income at Bejiharjo Village, Gunungkidul District, (2) to analyze capital, education, work hours and skill variables affect people’s income after village tourism program at Bejiharjo Village, Gunungkidul District. The research method use quantitative approach with descriptive analysis. The data taken is primary data obtained by interview respondents using questionnaires. The result of this study based on results of paired sample t-test showed the difference in people’s income between before and after the tourist village program. Capital, education, work hours and skill variables simultaneously affect the people’s income. Partially Capital, work hours and skill variables has positive effect and significant toward people’s income. While education variable does not affect the people’s income at Bejiharjo Village, Gunungkidul District.   Key words:Village Tourist Program, Poverty, People’s income.